Strategic Responsiveness: Peran Komisaris Independen Dan Struktur Kepemilikan - Eny Kusumawati; Erma Setiawati; Nursiam Nursiam; Nisrina Hanun Iftadi; Himawan Prasetyo (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2026)
An increasingly dynamic business environment driven by technological advancements, An increasingly dynamic business environment—driven by technological advancements, shifting customer needs, and sustainability demands—compels companies to develop the ability to respond quickly to change through strategic responsiveness. This study aims to examine the influence of corporate governance on strategic responsiveness, focusing on the role of independent directors, foreign shareholding, and institutional ownership. The study employs a quantitative approach using secondary data obtained from the annual reports of companies in six major industries representative of Indonesia’s economic dynamics—namely, energy, raw materials, manufacturing, infrastructure, technology, and primary consumer goods—listed on the Indonesia Stock Exchange for the 2022–2024 period. The research sample consists of 660 observations analyzed using panel data regression. The results indicate that independent directors have a positive effect on strategic responsiveness, foreign shareholding has no effect on strategic responsiveness, and institutional ownership has a negative effect on strategic responsiveness. These findings suggest that the effectiveness of corporate governance mechanisms in enhancing strategic responsiveness depends on the characteristics and roles of each corporate governance mechanism.